Charpy impact resistance of alkali treated curaua reinforced polyester composites - Ferreira,Ailton da Silva (2010)
Natural fibers obtained from cellulose-based plants are being used as reinforcement of polymer composite owing to both environmental and technical advantages. One important technical characteristic of most lignocellulosic fibers is the bend flexibility, which allows them to resist impact forces. As a consequence, there is an increasing application of these lignocellulosic fibers in automobile parts that, during a crash event, should absorb the impact energy without splitting into sharp pieces. The present work investigates the toughness behavior of polyester composites reinforced with up to 30% in volume of alkali treated continuous and aligned curaua fibers by means of Charpy impact tests. It was found that the incorporation of treated curaua fibers increased the composite absorbed impact energy but not as much as in composites reinforced with non-treated fibers. Macroscopic observation, and scanning electron microscopy analysis of fracture surface, revealed that the main mechanism for the increase in the Charpy notch toughness is the interfacial rupture between the curaua fiber and the polyester matrix.